Using the HAZOP procedure to assess a steam boiler safety system at a university hospital located in Brazil - Lucas de Oliveira, Marcos; Ruppenthal, Janis Elisa (Revista Gestão da Produção Operações e Sistemas, 2018)
The fierce competition between organizations has stimulated the production sector to improve its production processes simultaneously with the quality of its products, which, in short, heats up the economy and presents strong challenges to government agencies and employers, especially when considering the safety of employees in their workplace. The differential of this study is stated in the application of HAZOP in the boiler sector of a hospital, in other words, , in the micro industrial area of a company that provides services In this context, this paper aims to identify the risks present in the fire-tube boilers of the University Hospital of Santa Maria, RS. The method used follows the application practices of the HAZOP tool. Therefore, on this basis, we proceeded with bibliographic analysis, methodologies, references, on-site visits at the university hospital, and studies of investments made in steam generators. Due to this study, it was possible to show that the industry under study has no operation and maintenance default for the boiler, resulting in a high possibility of failure in the system as a whole and, in the case of an explosion, catastrophic consequences.